Principles of Organizing the Spiritual – Enlightenment Activities of Future Teachers - Rakhimov Asomiddin Anorboevich (Researchparks Publishing, 2021)
This article provides information on the specific factors of preparing future teachers for spiritual – enlightenment activities, the principles of preparation for innovative activities, explains the importance and role of these principles in the development of the student's personality. Also, the directions of the organization of spiritual and educational activities in higher education institutions were analyzed, conclusions and recommendations were given.